Improving English Language Teaching by Integrating Technology Instruction - Az-Zahra, Vahra Dilla; Sofendi, Sofendi; Petrus, Ismail (UNIB Press, 2024)
This research is aimed at finding out how is the implementation of technology-integrated instruction in English language teaching (ELT), the challenges that teacher and students encounter as well as the solutions to those challenges. A qualitative research methodology was employed in this study with a case study design. The interview, observation, and document review were used to get the answer of this research objective. The collected data were analyzed descriptively using an in-depth qualitative analysis. Data from observations had been collected using field notes and then summarized for analysis. The results of document review were summarized in order to help in compiling and analyzing the evaluation findings. The researcher used thematic analysis to analyze the interview data in order to make in-depth interpretation. The results showed that the implementation of technology-integrated instruction in ELT provides satisfaction among teacher and students. There are several benefits, including quick access to information, increased teaching and learning effectiveness, increased student engagement, creativity and enthusiasm. Furthermore, there were several challenges faced by both teachers and students, such as improved learning effectiveness, student engagement, and information accessibility. Despite the challenges, proactive problem solving and collaboration can lead the way for successful technology integration in ELT classrooms, creating an environment conducive to effective learning.